Risk Factors for Lead (Pb) And Cadmium (Cd) Exposure to Stunting in Toddlers: A Systematic Review - Rizky Aulia Salsabila AM; Suhartono Suhartono; Nurjazuli Nurjazuli (Jurnal Serambi Engineering, 2023)
AbstractStunting is a failure in growth due to insufficient nutritional intake in toddlers. Until now, stunting is still a health problem around the world, especially in developing and low-income countries. Stunting is not only caused by one factor but from many factors that are interrelated with each other, one of which is the contribution of lead and cadmium exposure which is associated with nutrient deficiency as a risk factor for stunting in toddlers. This study was conducted to assess the risk of exposure to Lead (Pb) and Cadmium (Cd). Literature searches are carried out through the journal sites Google Scholar, Garuda, Science Direct, Proquest, Scopus, JSTOR, PubMed. Article selection is carried out with criteria including bound variables are stunting events in toddlers, free variables are exposure to lead (Pb) and cadmium (Cd), open access full text, selected articles with a publication date of not more than the last 10 years (2012-2022), in Indonesian and English. Of the 574 relevant articles, 6 main articles showe the results that exposure to lead and cadmium in toddlers come from one of the factors, it is environmental and has an impact on the incidence of stunting in toddlers, due to the nature of heavy metals that are able to inhibit food nutrition and are directly proportional to cognitive decline in children. Factors related to stunting include the environment, gender, age, economic status and education of the motherKeywords: cadmium, lead, nutrition, stunting, toddlers